Fingerprint and Qr Code Based Authentication System at Pusat Servis Komputer JB - JAMAL, MUHAMMAD FADHLI; RAHIM, NORDIANA (Applied Information Technology And Computer Science, 2023)
With the rise in data breaches and identity theft, more robust authentication methods are clearly required. It occurs when someone steals another person's information and uses to commit fraud. Hence multifactor authentication is needed. It is an approach where requires user to present a combination of more than one credentials to verify identity. The fingerprint authentication and QR code was selected as an approach for this multifactor authentication system. It works by tracing the ridge and valley pattern on a finger, and a successful match indicates that an identity has been verified and thus access has been granted. QR code is a pattern represent different pieces of information. It is a data-encoded that can be scanned to authenticate the customer. This paper offered an overview of fingerprint and QR code-based authentication as a customer authentication system at Pusat Servis Komputer JB.